Answer
failed to answer the question
Solution
Sure, let's tackle each of these problems step by step.
---
## **ION 2**
### **Problem 7**
**Given:** An arithmetic sequence \( 7 ; x ; y ; -11 ; \ldots \)
**Find:** The values of \( x \) and \( y \).
**Solution:**
In an arithmetic sequence, the difference between consecutive terms is constant. Let's denote this common difference as \( d \).
Given the sequence:
- First term (\( a_1 \)) = 7
- Second term (\( a_2 \)) = \( x \)
- Third term (\( a_3 \)) = \( y \)
- Fourth term (\( a_4 \)) = -11
Using the property of arithmetic sequences:
\[
a_{n} = a_{1} + (n-1)d
\]
Let's find the common difference \( d \) using the first and fourth terms.
\[
a_4 = a_1 + 3d \\
-11 = 7 + 3d \\
-11 - 7 = 3d \\
-18 = 3d \\
d = -6
\]
Now, find \( x \) and \( y \):
\[
a_2 = a_1 + d = 7 + (-6) = 1 \\
a_3 = a_2 + d = 1 + (-6) = -5
\]
**Answer:**
- \( x = 1 \)
- \( y = -5 \)
---
## **Quadratic Number Pattern**
**Given Pattern:** \( -3 ; 6 ; 27 ; 60 ; \ldots \)
### **2.2.1 Determine the general term \( T_{n} = a n^{2} + b n + c \).**
**Solution:**
Assume the general term is quadratic:
\[
T_n = an^2 + bn + c
\]
We can set up equations using the given terms:
1. For \( n = 1 \):
\[
T_1 = a(1)^2 + b(1) + c = a + b + c = -3 \quad \text{(Equation 1)}
\]
2. For \( n = 2 \):
\[
T_2 = a(2)^2 + b(2) + c = 4a + 2b + c = 6 \quad \text{(Equation 2)}
\]
3. For \( n = 3 \):
\[
T_3 = a(3)^2 + b(3) + c = 9a + 3b + c = 27 \quad \text{(Equation 3)}
\]
Now, solve the system of equations.
**Subtract Equation 1 from Equation 2:**
\[
(4a + 2b + c) - (a + b + c) = 6 - (-3) \\
3a + b = 9 \quad \text{(Equation 4)}
\]
**Subtract Equation 2 from Equation 3:**
\[
(9a + 3b + c) - (4a + 2b + c) = 27 - 6 \\
5a + b = 21 \quad \text{(Equation 5)}
\]
**Subtract Equation 4 from Equation 5:**
\[
(5a + b) - (3a + b) = 21 - 9 \\
2a = 12 \\
a = 6
\]
**Substitute \( a = 6 \) into Equation 4:**
\[
3(6) + b = 9 \\
18 + b = 9 \\
b = -9
\]
**Substitute \( a = 6 \) and \( b = -9 \) into Equation 1:**
\[
6 - 9 + c = -3 \\
-3 + c = -3 \\
c = 0
\]
**Answer:**
\[
T_n = 6n^2 - 9n
\]
---
### **2.2.2 Calculate the value of the \( 50^{\text{th}} \) term of the pattern.**
**Solution:**
Using the general term \( T_n = 6n^2 - 9n \):
\[
T_{50} = 6(50)^2 - 9(50) = 6(2500) - 450 = 15000 - 450 = 14550
\]
**Answer:** \( T_{50} = 14,\!550 \)
---
### **2.2.3 Show that the sum of the first \( n \) first-differences of this pattern can be given by \( S_{n} = 6n^{2} + 3n \).**
**Solution:**
First, find the first difference sequence. The first difference \( D_n = T_n - T_{n-1} \).
Given \( T_n = 6n^2 - 9n \):
\[
D_n = T_n - T_{n-1} = [6n^2 - 9n] - [6(n-1)^2 - 9(n-1)]
\]
\[
D_n = 6n^2 - 9n - [6(n^2 - 2n + 1) - 9n + 9]
\]
\[
D_n = 6n^2 - 9n - 6n^2 + 12n - 6 + 9n - 9
\]
\[
D_n = (6n^2 - 6n^2) + (-9n + 12n + 9n) + (-6 - 9)
\]
\[
D_n = 12n - 15
\]
Now, find the sum of the first \( n \) first-differences:
\[
S_n = \sum_{k=1}^{n} D_k = \sum_{k=1}^{n} (12k - 15)
\]
\[
S_n = 12 \sum_{k=1}^{n} k - 15n
\]
\[
\sum_{k=1}^{n} k = \frac{n(n+1)}{2}
\]
\[
S_n = 12 \left( \frac{n(n+1)}{2} \right) - 15n = 6n(n+1) - 15n = 6n^2 + 6n - 15n = 6n^2 - 9n
\]
This contradicts the desired \( S_n = 6n^2 + 3n \). It seems there might be an error in the initial calculation.
Wait, let's re-examine the first difference calculation.
**Recalculating \( D_n \):**
Given \( T_n = 6n^2 - 9n \), then:
\[
D_n = T_n - T_{n-1} = (6n^2 - 9n) - [6(n-1)^2 - 9(n-1)]
\]
\[
= 6n^2 - 9n - [6(n^2 - 2n + 1) - 9n + 9]
\]
\[
= 6n^2 - 9n - 6n^2 + 12n - 6 + 9n - 9
\]
\[
= (6n^2 - 6n^2) + (-9n + 12n + 9n) + (-6 -9)
\]
\[
= 12n - 15
\]
Thus, \( D_n = 12n - 15 \).
Now, sum \( D_n \) from \( k=1 \) to \( n \):
\[
S_n = \sum_{k=1}^{n} (12k - 15) = 12 \sum_{k=1}^{n} k - 15n = 12 \cdot \frac{n(n+1)}{2} - 15n = 6n(n+1) - 15n = 6n^2 + 6n - 15n = 6n^2 - 9n
\]
But the problem states \( S_{n} = 6n^{2} + 3n \). There seems to be a discrepancy. However, considering the pattern provided:
Given the sequence: \( -3 ; 6 ; 27 ; 60 ; \ldots \)
Compute first differences:
\[
6 - (-3) = 9 \\
27 - 6 = 21 \\
60 - 27 = 33 \\
\]
Differences: 9, 21, 33,...
These differences themselves form an arithmetic sequence with a common difference of 12.
Thus, the sum of the first \( n \) differences:
\[
S_n = \sum_{k=1}^{n} (9 + 12(k-1)) = \sum_{k=1}^{n} (12k - 3) = 12 \cdot \frac{n(n+1)}{2} - 3n = 6n(n + 1) - 3n = 6n^2 + 6n - 3n = 6n^2 + 3n
\]
**Answer:**
\[
S_n = 6n^2 + 3n
\]
---
### **2.2.4 How many consecutive first-differences were added to the first term of the quadratic number pattern to obtain a term in the quadratic number pattern that has a value of 21,060?**
**Solution:**
We need to find \( n \) such that when adding the first \( n \) first-differences to the first term, the resulting term is 21,060.
Given:
- First term (\( T_1 \)) = -3
- Sum of first \( n \) first-differences (\( S_n \)) = 6n^2 + 3n
- Desired term (\( T \)) = 21,060
The relationship is:
\[
T = T_1 + S_n \\
21,060 = -3 + 6n^2 + 3n \\
6n^2 + 3n - 21,063 = 0 \\
\]
Divide the entire equation by 3 to simplify:
\[
2n^2 + n - 7,021 = 0
\]
Now, solve the quadratic equation \( 2n^2 + n - 7021 = 0 \).
Use the quadratic formula:
\[
n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
Where:
- \( a = 2 \)
- \( b = 1 \)
- \( c = -7,021 \)
Calculate the discriminant (\( \Delta \)):
\[
\Delta = 1^2 - 4(2)(-7021) = 1 + 56,168 = 56,169
\]
\[
\sqrt{56,169} = 237
\]
Now, find \( n \):
\[
n = \frac{-1 \pm 237}{4}
\]
We discard the negative solution as \( n \) must be positive:
\[
n = \frac{-1 + 237}{4} = \frac{236}{4} = 59
\]
**Answer:** 59 consecutive first-differences were added.
---
## **ION 3**
### **Problem**
**Given:** \( \sum_{k=1}^{\infty} 4 \cdot 3^{2 - k} \)
1. **Prove that it is a convergent geometric series. Show all your calculations.**
2. **If \( \sum_{k=p}^{\infty} 4 \cdot 3^{2 - k} = \frac{2}{9} \), determine the value of \( p \).**
### **Solution:**
#### **1. Prove that it is a convergent geometric series.**
**Identify the series:**
\[
\sum_{k=1}^{\infty} 4 \cdot 3^{2 - k}
\]
Simplify the general term:
\[
a_k = 4 \cdot 3^{2 - k} = 4 \cdot 3^2 \cdot 3^{-k} = 4 \cdot 9 \cdot \left(\frac{1}{3}\right)^k = 36 \cdot \left(\frac{1}{3}\right)^k
\]
Recognize the geometric series form:
\[
a_k = ar^{k}
\]
Comparing:
\[
ar^{k} = 36 \cdot \left(\frac{1}{3}\right)^k
\]
Thus, the first term when \( k = 1 \):
\[
a = 36 \cdot \left(\frac{1}{3}\right)^1 = 36 \cdot \frac{1}{3} = 12
\]
The common ratio is:
\[
r = \frac{1}{3}
\]
**Criteria for convergence of a geometric series:**
A geometric series \( \sum ar^{k} \) converges if \( |r| < 1 \).
Here, \( r = \frac{1}{3} \), and \( \left| \frac{1}{3} \right| < 1 \).
**Conclusion:**
Since \( |r| = \frac{1}{3} < 1 \), the series is convergent.
**Answer:** The series is a convergent geometric series because the common ratio \( r = \frac{1}{3} \) satisfies \( |r| < 1 \).
#### **2. Determine the value of \( p \) if \( \sum_{k=p}^{\infty} 4 \cdot 3^{2 - k} = \frac{2}{9} \).**
**Solution:**
Given:
\[
\sum_{k=p}^{\infty} 4 \cdot 3^{2 - k} = \frac{2}{9}
\]
Simplify the series:
\[
\sum_{k=p}^{\infty} 4 \cdot 3^{2 - k} = \sum_{k=p}^{\infty} 36 \cdot \left(\frac{1}{3}\right)^k
\]
This is a geometric series with:
\[
a = 36 \cdot \left(\frac{1}{3}\right)^p \quad \text{and} \quad r = \frac{1}{3}
\]
The sum of an infinite geometric series starting from \( k = p \):
\[
S = \frac{a}{1 - r} = \frac{36 \cdot \left(\frac{1}{3}\right)^p}{1 - \frac{1}{3}} = \frac{36 \cdot \left(\frac{1}{3}\right)^p}{\frac{2}{3}} = 36 \cdot \left(\frac{1}{3}\right)^p \cdot \frac{3}{2} = 54 \cdot \left(\frac{1}{3}\right)^p
\]
Set this equal to \( \frac{2}{9} \):
\[
54 \cdot \left(\frac{1}{3}\right)^p = \frac{2}{9}
\]
Divide both sides by 54:
\[
\left(\frac{1}{3}\right)^p = \frac{2}{9} \div 54 = \frac{2}{9 \times 54} = \frac{2}{486} = \frac{1}{243}
\]
Express \( \frac{1}{243} \) as \( \left(\frac{1}{3}\right)^5 \) since \( 3^5 = 243 \):
\[
\left(\frac{1}{3}\right)^p = \left(\frac{1}{3}\right)^5
\]
Therefore:
\[
p = 5
\]
**Answer:** \( p = 5 \)
---
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution